Incidence and Impact of Dysglycemia in Patients with Sepsis Under Moderate Glycemic Control. Issue 4 (October 2021) - Fujishima, Seitaro; Gando, Satoshi; Saitoh, Daizoh; Kushimoto, Shigeki; Ogura, Hiroshi; Abe, Toshikazu; Shiraishi, Atsushi; Mayumi, Toshihiko; Sasaki, Junichi; Kotani, Joji; Takeyama, Naoshi; Tsuruta, Ryosuke; et al.
Abstract : ABSTRACT: Glycemic control strategies for sepsis have changed significantly over the last decade, but their impact on dysglycemia and its associated outcomes has been poorly understood. In addition, there is controversy regarding the detrimental effects of hyperglycemia in sepsis. To evaluate the incidence and risks of dysglycemia under current strategy, we conducted a preplanned subanalysis of the sepsis cohort in a prospective, multicenter FORECAST study. A total of 1, 140 patients with severe sepsis, including 259 patients with pre-existing diabetes, were included. Median blood glucose levels were approximately 140 mg/dL at 0 and 72 h indicating that blood glucose was moderately controlled. The rate of initial and late hyperglycemia was 27.3% and 21.7%, respectively. The rate of early hypoglycemic episodes during the initial 24 h was 13.2%. Glycemic control was accompanied by a higher percentage of initial and late hyperglycemia but not with early hypoglycemic episodes, suggesting that glycemic control was targeted at excess hyperglycemia. In nondiabetic patients, late hyperglycemia (hazard ratio, 95% confidence interval; P value: 1.816, 1.116–2.955, 0.016) and early hypoglycemic episodes (1.936, 1.180–3.175, 0.009) were positively associated with in-hospital mortality. Further subgroup analysis suggested that late hyperglycemia and early hypoglycemic episodes independently, and probably synergistically, affect the outcomes. In diabetic patients, however, these correlations were not observed. In conclusion, a significantly high incidence of dysglycemia was observed in our sepsis cohort under moderate glycemic control. Late hyperglycemia in addition to early hypoglycemia was associated with poor outcomes at least in nondiabetic patients. More sophisticated approaches are necessary to reduce the incidence of these serious complications. Abstract : Supplemental Digital Content is available in the text